Disruption of DMD gene leads to altered calcium homeostasis and metabolic shift impacting gastric Cancer cell proliferation and migration - Xiaodong Zou; Tong Wu; Tao Su; Hui Xiao; Chuyan Ni; Lijuan Hu; Wenchu Lin; Weilin Chen; Richard D Ye; Jianjiao Lin; Li Xiang (Cancer Cell International)
Abstract Background DMD gene has been implicated in the progression and development of several tumors, but its specific contribution to gastric cancer (GC) has not been fully elucidated. Methods We validated DMD gene expression levels in the TIMER2.0 database and human gastric cancer tissue microarrays and constructed gastric precancerous lesion mouse models and DMD gene knockout and overexpression cell lines to investigate the role of DMD gene in gastric cancer development. Results In this study, we found that DMD gene is significantly downregulated in GC cells and tissues. Mechanistic analysis revealed that DMD gene deletion increased intracellular calcium levels, disrupted mitochondrial homeostasis, and promoted a metabolic shift towards glycolysis, impacting GC cell proliferation and migration. Conclusions Taken together, our results shed light on the novel role of DMD gene in gastric cancer development and provide valuable insights into potential therapeutic strategies.